Analisis Pelatihan e-Modul Tematik di SD Bellarminus Bekasi - Katerina Winiharti (Medan Resource Center, 2022)
The Covid-19 virus outbreak has been going on for almost two years with a high number of spreading cases, making the government try hard to deal with this outbreak by breaking the chain of transmission by making new habits in this new normal era. All aspects of life are affected, including in the world of education. The Ministry of Education issued a circular letter from the Minister of Education and Culture No. 4 of 2020 regarding the policy of learning to be done from home. However, in its journey distance learning is seen as less effective. Therefore, the government requires schools to provide the Limited Face-to-face Learning (PTMT) option if all teachers and educators have been vaccinated. SD Bellarminus itself in holding PTMT uses hybrid learning where the implementation of face-to-face learning is carried out simultaneously with online learning for students who are not willing to do PTMT. To support this, the use of e-modules is felt to be very necessary. Training on making e-modules is carried out to support the use of e-modules at Bellarminus Elementary School Bekasi